1993
DOI: 10.1108/01437739310047010
|View full text |Cite
|
Sign up to set email alerts
|

Why Can′t Men Lead Like Women?

Abstract: While some women have emerged as leaders within contemporary organizations, they occupy one‐third of managerial and professorial positions in Canada while composing approximately one‐half of the workforce. At top managerial levels, they occupy less than 5 per cent of senior positions. Earlier research identified “female deficiencies” as a reason why few women have made it to the top. Other findings have indicated that following a masculine model has both advantages and disadvantages for aspiring women managers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…The use of an androgynous leadership model has not yielded significant findings but there are common characteristics of successful leaders combining both the masculine and feminine models. Organizations and their top leaders need to expand their definition of effective leadership so that an interactive style can be valued, allowing these organizations the necessary flexibility, key to surviving within an increasingly competitive and diverse environment (Appelbaum and Shapiro, 1993).…”
Section: Gender Rolementioning
confidence: 99%
“…The use of an androgynous leadership model has not yielded significant findings but there are common characteristics of successful leaders combining both the masculine and feminine models. Organizations and their top leaders need to expand their definition of effective leadership so that an interactive style can be valued, allowing these organizations the necessary flexibility, key to surviving within an increasingly competitive and diverse environment (Appelbaum and Shapiro, 1993).…”
Section: Gender Rolementioning
confidence: 99%
“…Over the years women are acquiring leadership roles, and it is important for organizations to recognize the differences between males and female leaders. As Applebaum and Shapiro (1993) observed that women have a different style of leading compared to men. It is equally critical to understand that these differences are very likely to influence the commitment of employees towards their organization.…”
Section: Transformational Leadership and Organizational Commitmentmentioning
confidence: 99%
“…Furthermore, adding to the long discussion regarding the effects of environmental vs. individual differences in the work context, in the current paper, we investigate both situational and individual factors engaging LMX in the role of a mediator variable while gender was invoked as a moderator variable. Gender's effect is particularly important because previous research has indicated that women tend to display different leadership styles than men (e.g., Barsheshet-Picer and Tziner, 2014), that is, democratic and participative styles of leadership to a greater degree than men (Eagly and Johnson, 1990;Appelbaum and Shapiro, 1993;van Engen and Willemsen, 2004;Eagly, 2005;Eagly and Carli, 2007). Figure 1 portrays the overall research model.…”
Section: Introductionmentioning
confidence: 99%
“…There is good reason to examine further linkages between gender, LMX, and job-related outcomes. Many scholars suggest that men and women use basically the same mechanisms to create leader behaviors, but there are also subtle, true distinctions (Powell, 1990;Appelbaum and Shapiro, 1993;Eagly, 2005). Specifically, in spite of an amount of gender bias in measuring and defining leadership, there appears to be a basic female leadership style that tends toward a democratic style of relationship enhancement with cooperative and participative leadership behaviors (Eagly and Carli, 2003;Rosener, 2011).…”
Section: Introductionmentioning
confidence: 99%